ANALISA MACAM PUPUK CAIR DAN VARIETAS TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TOMAT (Lycopersicum esculentum M.) - Danang Hermanto; Ana Amiroh; Dian Eka Kusumawati (Agroteknologi Fakultas Pertanian Universitas Islam Darul 'Ulum (UNISDA), 2022)
Tomato plants are vegetable plants that have been cultivated for hunderds of years, but it is not known for sure when it started spreading. The purpose of this study was to determine the effect of liquid fertilizers and varieties on the growth and yield of tomato plants. The hypothesis of this research is that using NASA POC liquid fertilizer and the Agatha F1 variety will produce the best production on tomato plants. This research was conducted using a factorial randomized block design (RAK) method, which consisted of two factors. From these two factors, 9 treatment combinations were obtained and 3 replications were obtained. Parameters observed in the vegetative phase include: plant height, number of leaves and stem diameter. Parameters observed during the generative phase include: the number of flowers and the number of fruit planted. The data obtained from the observations were calculated by analysis of variance with the fisher test ( F test at 5% level ), if there is a significant difference, it will be continued with the smallest 5% significant difference test. The result of variance showed that there was an interaction in the vegetatife phase dominated by the treatment of Agatha F1 and POC NASA varieties which affected plant height at the age of 21, 28, 36 and 43 and number of leaves at the age of 36 and 43. In the generative phase there are the best yields were obtained from the combination treatment of Agatha F1 and POC NASA.